2021
DOI: 10.1080/08941939.2021.1933272
|View full text |Cite
|
Sign up to set email alerts
|

Local Steroid Treatment: An Effective Procedure for Idiopathic Granulomatous Mastitis, Including Complicated Cases

Abstract: Purpose To evaluate the effectiveness of treatment with topical and intralesional steroids for idiopathic granulomatous mastitis (IGM) and to compare with surgical methods. Methods Data was retrospectively collected from records. Intralesional steroid injection and topical steroid administration, hereafter referred to as local steroid treatment (LST) were applied in Group 1. Surgery (local excision, wide excision and mastectomy) was performed in Group 2. In Group 1 changes in lesion sizes were recorded and fac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…However, systemic side effects were observed at a very low rate, as 9.4% of the patients received systemic treatment, which might be due to the relatively shorter duration of systemic exposure to steroids for a maximum of 3 months in their study. Ertürk et al further reported that 2 of 38 patients developed hematoma after LSI ( 23 ). However, patients in other reports and in the present study were found to have a higher rate of steroid-related systemic side effects, even though patients in our study were treated with a low-dose peroral steroid regimen for a maximum period of >6 months in a few cases in the systemically treated group.…”
Section: Discussionmentioning
confidence: 98%
“…However, systemic side effects were observed at a very low rate, as 9.4% of the patients received systemic treatment, which might be due to the relatively shorter duration of systemic exposure to steroids for a maximum of 3 months in their study. Ertürk et al further reported that 2 of 38 patients developed hematoma after LSI ( 23 ). However, patients in other reports and in the present study were found to have a higher rate of steroid-related systemic side effects, even though patients in our study were treated with a low-dose peroral steroid regimen for a maximum period of >6 months in a few cases in the systemically treated group.…”
Section: Discussionmentioning
confidence: 98%
“…Healing of the disease with no recurrence in patient follow-up constitutes effective therapy of GM [ 76 ]. Surgical excision, including wide surgical resection, mastectomy with or without rapid breast reconstruction, frequent abscess drainage, antibiotics, topical or systemic corticosteroids treatment, immunosuppression with MTX, and close observation are among the treatment options [ 15 , 37 , 41 , 43 ]. Several studies suggest that the disease will improve by itself through Observation alone [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology and pathogenesis of GLM are still poorly understood. Current surgical procedures and medical treatments for GLM are frequently accompanied by numerous complications and a high recurrence rate ( 20 , 21 ). In recent years, technologies such as noninvasive biomarkers and miRNA chips have emerged, which may contribute to the diagnosis of diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs for the treatment of GLM are currently under investigation. Although no consensus has been reached on the selection of drugs, corticosteroids ( 20 , 25 , 26 ) and methotrexate ( 27 , 28 ) have been widely used in the treatment of GLM. GLM is considered to be an autoimmune inflammatory disease due to the marked clinical treatment effect of immunosuppressants.…”
Section: Discussionmentioning
confidence: 99%